KESIAPSIAGAAN SEKOLAH DITINJAU DARI KETERSEDIAAN SARANA PRASARANA PENDUKUNG DALAM MENGHADAPI BENCANA DI KOTA BANDA ACEH - Dahniar, Salsabila; M. Hafizul, M. Hafizul (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
Availability of infrastructure is very important in efforts to reduce disaster risk, especially in education units. Schools that have adequate infrastructure can minimize the impact of disasters. The purpose of this study was to determine school preparedness in terms of the availability of supporting infrastructure in dealing with disasters in Banda Aceh City. This research uses a quantitative descriptive approach with a survey research type. The sampling technique used Cluster Sampling with a total sample of 9 schools from various levels of education. Data collection was carried out using a questionnaire with a Guttman scale. The data analysis technique uses a simple percentage formula. The results of the study show that, as a whole, schools in Banda Aceh City are generally in the ready category as seen from the availability of infrastructure in dealing with disasters with a percentage of 83.3%.